The Progressivity of Umar Ibn Al-Khattab's Ijtihad in Responding to Community Social Changes - Arrasyid, Fauzan; Pagar, Pagar; Tanjung, Dhiauddin; Nor, Mohd Roslan Mohd (AL-ISTINBATH : Jurnal Hukum Islam, 2023)
This study aims to see how Umar Ibn Al-Khattab's legal ijtihad typology responds to social changes that occur in society. Ijtihad is a legal decision-making process based on syar'i arguments. During his leadership, Umar ibn Khattab was known to history as one of the caliphs who often performed ijtihad and the results often differed from those of other companions of the Prophet in terms of understanding and practice of Islamic law. Umar bin Khattab often recited the Quranic texts and hadith of the Prophet by contextualizing verses and hadiths through his maqasid approach.Â  This research uses normative legal research methods. The data were obtained through literature review and analyzed using a descriptive analysis approach. The results showed that Umar's ijtihad pattern of Islamic law in some cases is considered as an integrated, integral, and authentic understanding in order to realize the benefit of Muslims. He carried out the policy of Islamic law by paying attention to rapidly developing social changes. Although his Ijtihad seems contrary to the provisions of the text, in fact Umar can be said to be able to understand the general principles (al-ushul al-kulliyat) of the Koran.Â  So that the Quranic text, which has descended historically, can always provide answers and solutions to social problems of society that are always undergoing changes.